Review of Community Based Organization and Community Pharmacy Partnerships for Preventive Care Services - Valerie Lindell; Sarah E. Kelling (University of Minnesota Libraries Publishing, 2018)
Collaborative care has been widely recognized as being critical to promoting the health of individuals and populations.  It is hypothesized that the development of partnerships between community-based organizations and community pharmacies may result in increased access to preventive care services for community members with the goal of improving health outcomes.  The purpose of this review was to identify and describe partnerships between community-based organizations and community pharmacies.  A literature search was conducted for all articles in the English language published through January 2018 that included these types of partnerships offering preventive care services.  A total of seven articles were included in the review, of which the majority were conducted in the United States (n=5). Community-based organizations included businesses, community health centers, local associations, public health departments, schools, and workplaces.  Preventive care services that were offered included blood pressure and cardiovascular risk assessment, diabetes management, flu ready card and HIV self-test kit voucher distribution and education, and bone mineral density screenings.  The limited literature suggests that additional opportunities should be explored in order for community-based organizations and community pharmacies to partner in order to provide and evaluate the impact of preventive care services in the community setting. Conflict of Interest:  We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties. Type: Review